Store-Operated Calcium Entry via STIM1 Contributes to MRGPRX2 Induced Mast Cell Functions - Occhiuto, Christopher J.; Kammala, Ananth K.; Yang, Canchai; Nellutla, Rithvik; Garcia, Marco; Gomez, Gregorio; Subramanian, Hariharan (Frontiers in Immunology, 2020)
Mast cells are inflammatory immune cells that play an essential role in mediating allergic reactions in humans. It is well known that mast cell activation is critically regulated by intracellular calcium ion (Ca2+) concentrations. MAS-related G-protein coupled receptor-X2 (MRGPRX2) is a G-protein coupled receptor (GPCR) expressed on mast cells that is activated by various ligands, including several FDA approved drugs; consequently, this receptor has been implicated in causing pseudo-allergic reactions in humans. MRGPRX2 activation leads to an increase in intracellular Ca2+ levels; however, the Ca2+ mobilizing mechanisms utilized by this receptor are largely unknown. Previous reports showed that store-operated Ca2+ entry (SOCE) via the calcium sensor, stromal interaction molecule 1 (STIM1), regulates mast cell response induced by the high-affinity IgE receptor (FcεRI). In this study, using complementary pharmacologic and genetic ablation approaches we demonstrate that SOCE through STIM1 promotes MRGPRX2-induced human mast cell response in vitro. Importantly, SOCE also critically modulates MrgprB2 (mouse ortholog of human MRGPRX2) dependent inflammation in in vivo mouse models of pseudo-allergy. Collectively, our data suggests that MRGPRX2/MrgprB2 activation of mast cells is dependent on SOCE via STIM1, and further characterization of the MRGPRX2-SOCE-STIM1 pathway will lead to the identification of novel targets for the treatment of pseudo-allergic reactions in humans.